Response of Watermelon to Drought Stress and Its Drought-Resistance Evaluation - Kaili Ren; Taoxia Tang; Weiping Kong; Yongquan Su; Yuping Wang; Hong Cheng; Yonggang Yang; Xiaoqin Zhao (Plants)
This study investigated the response of watermelon seedlings to drought stress by assessing the growth, physiological, and biochemical indices using a pot-based continuous drought method. Drought stress indices, phenotypic plasticity indices, and membership function values were calculated, followed by a correlation analysis, principal component analysis, and cluster analysis, to comprehensively evaluate the drought resistance of 13 watermelon genotypes. The results revealed that drought stress significantly reduced the fresh and dry weights, root length, root area, root volume, root tips, and forks of watermelon seedlings. Additionally, drought significantly reduced the relative water content of leaves and increased the levels of osmotic-adjustment substances (soluble sugars, soluble proteins, proline, and starch). Persistent drought also modulated the activities of antioxidant enzymes (SOD, POD, and CAT), leading to oxidative stress through the accumulation of H2O2. Membrane damage, indicated by a significant increase in the MDA content and relative conductivity, was observed, adversely affecting seedling growth. Phenotypic plasticity indices indicated that watermelon exhibits strong adaptability to drought. Cluster analysis categorized the 13 genotypes into four groups: highly drought-resistant (14X5), drought-resistant (LK13, JLR, HXF1, 14X4, 14X1, and 14X6), low drought-resistant (21F05, JH1, JR3, 14X7, and 16F02), and drought-sensitive (16C07). This study provides valuable genetic resources for breeding drought-resistant watermelon varieties.